Photometry , photometric sizes and their application and of photometry main methods School Students - Erkinova Mokhlaroyim (Genius Journals, 2024)
This in the article photometry , photometric their sizes application and of photometry main methods about data given . In particular , light energy , his direction and to him depends was sizes about concepts there is
Keywords: Photometry; photometric sizes; light flow